2019
DOI: 10.1111/mice.12485
|View full text |Cite
|
Sign up to set email alerts
|

An ensemble machine learning‐based modeling framework for analysis of traffic crash frequency

Abstract: This study is, to our knowledge, the first in the literature to introduce a modeling framework for analyzing traffic crash frequency based on a series of ensemble machine learning (EML) methods. The main objectives of this study are fourfold: (a) to design a systematic EML‐based framework for crash frequency analysis, (b) to comprehensively compare the performance in analyzing crash frequency by different optimized EML models, (c) to identify significant contributors to crash frequency, and (d) to propose the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 86 publications
(112 reference statements)
0
17
0
Order By: Relevance
“…ML has also been used in the field of structural health monitoring to analyze vibration response of structures and detection of anomalies extracted from sensors (Azimi & Pekcan, 2020; Gulgec, Takáč, & Pakzad, 2020; Ni, Zhang, & Noori, 2019). DL has also been used to help analyze traffic crash data (X. Zhang, Waller, & Jiang, 2020), analyze crack patterns in concrete structures (Cha, Choi, & Büyüköztürk, 2017; Okazaki, Okazaki, Asamoto, & Chun, 2020), and conduct reliability analysis on infrastructure networks (Nabian & Meidani, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…ML has also been used in the field of structural health monitoring to analyze vibration response of structures and detection of anomalies extracted from sensors (Azimi & Pekcan, 2020; Gulgec, Takáč, & Pakzad, 2020; Ni, Zhang, & Noori, 2019). DL has also been used to help analyze traffic crash data (X. Zhang, Waller, & Jiang, 2020), analyze crack patterns in concrete structures (Cha, Choi, & Büyüköztürk, 2017; Okazaki, Okazaki, Asamoto, & Chun, 2020), and conduct reliability analysis on infrastructure networks (Nabian & Meidani, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ensemble methods are a class of powerful machine learning techniques that combine multiple learners for the same task. It is commonly acknowledged that an ensemble is usually significantly more accurate than a single learner (Zhang, Waller, & Jiang, 2020; Z. Zhou, 2012). In this work, we adopt a training procedure called SWA (Izmailov, Podoprikhin, Garipov, Vetrov, & Wilson, 2018), which serves as an implicit model ensemble method, to boost our model performance.…”
Section: Methodsmentioning
confidence: 99%
“…Ensemble methods are a class of powerful machine learning techniques that combine multiple learners for the same task. It is commonly acknowledged that an ensemble is usually significantly more accurate than a single learner (Zhang, Waller, & Jiang, 2020;Z. Zhou, 2012).…”
Section: Model Ensemblementioning
confidence: 99%
“…Such algorithms have as input a set of roadway-, users-, vehicles-, and environment-related features of the network analyzed. Commonly, they aimed at predicting the crash frequency for stretches of road or intersections using different types of algorithms: k-nearest neighbor [5], support vector machine [6], and tree-based models, such as classification and regression tree, M5-tree, RF, extremely randomized trees, and gradient tree boosting [7][8][9]. Moreover, there are studies [10,11] in which the authors suggested the use of neural networks.…”
Section: Machine Learning Algorithms In Road Safety Analysesmentioning
confidence: 99%